Systematic Review of Literature on Eating Disorders During Pregnancy—Risk and Consequences for Mother and Child - Janas-Kozik, Małgorzata; Żmijowska, Anna; Zasada, Ida; Jelonek, Ireneusz; Cichoń, Lena; Siwiec, Andrzej; Wilczyński, Krzysztof M. (Frontiers in Psychiatry, 2021)
Background: Eating disorders (ED) are a diagnostic category that includes several nosological units such as anorexia nervosa (AN), bulimia nervosa (BN), or binge eating disorder (BED). This category most often concerns women, while the peak incidence falls on the reproductive age. Therefore the issue of ED during pregnancy is an interesting topic. Due to the creation of unrealistic ideal of “desired”, slim figure both by the mass media and social media even during and right after gestation, more and more pregnant women introduce behaviors aimed at maintaining the "perfect" appearance. However in some cases it may have serious consequences for the health of both mother and child leading to the creation of the term "pregorexia" by the media to describe this issue. Aim: The aim of this paper was to conduct a systematic review of the literature dealing with eating disorders in pregnant women, with particular emphasis on pregorexia. Method: A systematic review of literature published within the last 5 years (2016-2021) in English or Polish and available through MEDLINE / PubMed, Google Scholar and Cochrane Library databases was conducted based on the previously assumed inclusion and exclusion criteria. Results: Initially, 634 publications were obtained during the review, of which 55 papers were selected in the course of the title analysis. After further evaluation of abstracts, 28 papers were qualified for full text analysis. Ultimately, 10 papers were selected for the final analysis. Conclusions: The issue of ED in pregnant women is a broad topic covering a heterogeneous group of women - both those with a previous history and those with the onset during pregnancy. The occurrence of ED symptoms during this period is associated with a high likelihood of negative consequences for both the mother and the child. The course of pregnancies and deliveries in these patients is more complicated. Therefore, it seems reasonable to develop a multidisciplinary screening strategy and standards of management and supervision over this group of patients.